2010
DOI: 10.1111/j.1463-1326.2009.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA pretreatment protects myocardium against ischaemia/reperfusion injury through the phosphatidylinositol 3‐kinase/Akt‐dependent pathway in diabetic rats

Abstract: This study indicates that TSN pretreatment reduces infarct size and improves cardiac dysfunction after I/R injury in diabetic rats. This was accompanied with decreased cardiac apoptosis and inflammation. The possible mechanism responsible for the effects of TSN is associated with the PI3K/Akt-dependent pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 25 publications
(30 reference statements)
6
52
0
Order By: Relevance
“…For instance, the pervasive effects of Tanshinone and Berberin in the prevention and cure of common cardiovascular diseases has been clarified [7,8]. In the current study, Aloeemodin (Fig.…”
Section: Introductionmentioning
confidence: 63%
“…For instance, the pervasive effects of Tanshinone and Berberin in the prevention and cure of common cardiovascular diseases has been clarified [7,8]. In the current study, Aloeemodin (Fig.…”
Section: Introductionmentioning
confidence: 63%
“…7,8 TSA has a multi-dimensional beneficial actions on the cardiovascular system through anti-atherosclerosis, anti-arrhythmia, anti-inflammation, anti-smooth muscle hyperplasia, anti-myocardial hypertrophy, and so on. [9][10][11][12] The protective effect of TSA on impairment of myocardium has been extensively reported, [13][14][15][16] and the cardioprotection is mainly related to anti-apoptosis of cardiomyocytes. [17][18][19] However, its detailed mechanism for anti-apoptosis has not been fully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that tanshinone IIA protects cardiac myocytes against oxidative stress-triggered damage and apoptosis (16), prevents myocardial hypertrophy (17), protects against sudden cardiac death (18) and attenuates myocardial ischemic (19) and reperfusion injury (20). However, the majority of studies (7,20) have focused on applying tanshinone IIA prior to ischemia, which limits its use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that tanshinone IIA protects cardiac myocytes against oxidative stress-triggered damage and apoptosis (16), prevents myocardial hypertrophy (17), protects against sudden cardiac death (18) and attenuates myocardial ischemic (19) and reperfusion injury (20). However, the majority of studies (7,20) have focused on applying tanshinone IIA prior to ischemia, which limits its use in clinical practice. In the present study, the clinical application of tanshinone IIA was widened, as the data obtained demonstrate that when applied prior to prolonged reperfusion following sustained ischemia, tanshinone IIA at both medium and high doses, which have been used in other studies for cardioprotection, resulted in a reduction in infarct size comparable to that of ischemic postconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation